STCW Convention Compliance in Maritime Education: Bridging International Regulatory Standards and National Implementation Challenges - Baihaqi; Kurniawan, Dedi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
This research critically examines implementation challenges of STCW Convention requirements in maritime education institutions across developing nations, focusing on gaps between international competency standards mandated by IMO's 2010 Manila Amendments and actual training delivery in resource-constrained maritime academies. Through qualitative analysis of 20 maritime education administrators, 18 maritime instructors, and 17 recent maritime graduates across five developing maritime nations, the study identifies systemic implementation barriers including inadequate simulation facilities (cited by 85% of participants), instructor qualification gaps (78%), and administrative compliance challenges (72%). Thematic analysis reveals critical tensions between internationally prescribed competency-based training approaches and institutional realities of limited resources, outdated infrastructure, and insufficient quality assurance mechanisms. Document analysis of curriculum frameworks and assessment methodologies from 12 maritime education institutions demonstrates substantial variation in STCW implementation quality, with only 33% achieving comprehensive compliance across all convention requirements. The research proposes a contextually-adaptive compliance framework addressing regional resource constraints while maintaining international standards integrity. Findings provide evidence-based recommendations for maritime authorities, flag state administrations, and educational institutions to achieve effective STCW compliance producing competent seafarers meeting global shipping industry requirements.